Allelopathic and auto-toxic effects of aqueous extracts of Codonopsis pilosula root secretions - Daiyu Qiu; Xue Wang; Fengbin Xu; Qian Li; Fengying Ren; Kan Jiang (PLoS ONE, 2025)
Water-soluble constituents in the root exudates of C. pilosula exhibit both allelopathic and auto-toxic properties, which substantially impede its growth. To mitigate the constraints associated with the continuous cropping of C. pilosula, this study examined the impact of aqueous extracts from the root exudates at various developmental stages on seed germination and seedling growth. Additionally, we isolated and characterized significant auto-toxic allelochemicals. Our findings revealed that the inhibitory effects on seed germination, seedling growth, and the activity of antioxidant enzymes-collectively referred to as a comprehensive effect-intensified progressively with increasing concentrations of the aqueous extracts from C. pilosula root exudates. The most pronounced auto-toxic comprehensive effect was observed with extracts at a concentration of 50 mL during the reproductive phase, diminishing SOD and POD activities, and MDA levels in C. pilosula seedlings by 72.3%, 71.7%, and 83.3% respectively, compared to the control (P<0.05). Three primary allelopathic compounds-acetic acid, hexamethyl cyclotrisiloxane, and methoxybenzene oxime were isolated and identified in the aqueous extracts. Acetic acid, constituting 44.1% of the total chemical profile, exhibited a significant inhibitory effect on seed germination and seedling growth (P<0.05). In conclusion, the aqueous extracts of C. pilosula root exudates significantly inhibit seed germination and seedling growth, especially during the plant’s reproductive stage, with low molecular weight organic acids being the predominant allelopathic components.